Confirmatory Factors Analysis of the Learning Ecosystem Towards Desired Outcomes of Learners - Samyong, Radchadaporn; Manokarn, Monnapat; Damrongpanit, Suntonrapot (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024, 2024)
This research aims to analyze the confirmatory components and verify the congruence of the model indicators of learning ecosystem towards desired outcomes of learners in basic education. The sample group consists of 500 individuals, including school administrators and teachers attached to the Basic Education Office, selected through stratified random sampling based on school sizes and geographical regions. The research tool is a questionnaire assessing factors influencing the desired outcomes of learners at the basic education level, employing a 5-point Likert scale. The validity of the questionnaire was confirmed through content validation by five experts in educational administration and measurement, yielding an index of congruence ranging from 0.80 to 1.00. The reliability coefficient using Cronbach’s alpha was 0.969.           The results of the Confirmatory Factor Analysis (CFA) using Mplus program revealed two key findings: 1) The components of the learning ecosystem consist of 5 factors with their respective standardized factor loadings: Learning Culture (β = 0.989) emerged as the strongest factor, followed by Stakeholder Support (β = 0.951), Learning Resources (β = 0.863), Content (β = 0.805), and Educational Policy (β = 0.709), 2) The confirmatory factor analysis demonstrated that the model fits well with the empirical data, validating the theoretical framework of learning ecosystem components in basic education context. These findings suggest that learning culture and stakeholder support are crucial elements in developing an effective learning ecosystem for achieving desired learner outcomes in basic education. Keywords: Learning Ecosystem, Desired Outcomes of Learners, Confirmatory Factor Analysis, Basic Education